Individual sources, dynamics, and expressions of emotion - Zerbe, W. J.; Ashkanasy, Neal M.; Härtel, Charmine E. J., 1959- (Research on emotion in organizations ;, 2013)
Research on emotion in organizations is the publication of the Emonet listserv http://www.emotionsnet.org, which hosts the biennial International Conference on Emotion and Worklife. Chapters in the series include a selection of peer-reviewed papers from the conference, together with invited chapters by leading scholars in the field of emotion in organizational settings.